Pengelolaan Pembelajaran IPA Ditinjau Dari Hakikat Sains Pada SMP Di Kabupaten Lombok Timur - Lalu Usman Ali (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2018)
This study aimed to describe (1) the teachers understanding on the nature of science, (2) the application of the nature of science in teaching science, (3) the barriers ocoured during its implementation and (4) the solutions which was done to solve the learning problems. Designed as qualitative research, this closed to case study approach. This study in teaching learning process at the junior high school in SMP Negeri 1 Selong, SMP Negeri 1 Terara, and SMP Negeri 1 Masbagik. The data were collected trought observation, interview, questionnaires, and documentations. Triangulation is used to assess the credibility, truth, relevancy of the data and was done using Miles and Huberman intractive model of data analysis. The findings of the study showed (1) the teachers have low understanding about nature of science, (2) the teachers was seldom in applying the nature of science in learning process (25,0%), (3) the barriers found by the teachers was inapropriate of the subject materials with time managements, aspects of cognition oriented, students’ mental readiness and the teachers is not understanding of the nature of science, and (4) the teachers dominantly used discussion and speech methods than used inquiry methode in teaching learning process.